PERANAN PROGRAM GERAKAN TERPADU PENGENTASAN KEMISKINAN (GERDU TASKIN) DALAM PEMBERDAYAAN MASYARAKAT PEDESAAN DI KECAMATAN PETERONGAN KABUPATEN JOMBANG - Widodo, Mochammad Heru (Fakultas Ekonomi Universitas Darul 'Ulum Jombang, 2015)
This research attempats to analyze the impact of the poverty eradication through rural empowerment program ( hereafter called Gerdu Taskin ) in the village  Sumberagung dsubistrid Peterongan regency of Jombang , this research also identifies the impacts of such programs on the people receiving the funds. The data used in this research are primary data obtained from the respondents chosen through random sampling in those subdistricts, 50 respondents were from village Sumberagung of Peterongan Subdistrict. The analysis methods applied in this research are simple mathematical and statistical analysis, and qualitative analysis. The findings of the research indicate that the program in the regency of Jombang were impacts and have positif impacts. These programs empower the economy of the poor in those two subdistrict so that their income increases, absorb more labor, decrease the number of poor in those villages. Finally there are increasing concerns of the non poor toward the poor and increasing concerns of the community at large about the income inequaluties.